Analysis of Clinical Manifestations and Imaging of COVID-19 Patients in Intensive Care. (23rd June 2022) - Li, Lihong; Yao, Yongwei; Feng, Xiaofei; Chen, Lingling; Wu, Rui; Chang, Yuejin; Lou, Qiaoqin; Pan, Jinbo; Wang, Zhangli
Abstract : Objective . The study aims to summarize and analyze the clinical and CT findings of severe COVID-19 patients. Methods . From February 11 to March 31, 2020, 61 COVID-19 patients in intensive care in the E1-3 ward of Tongji Hospital were analyzed retrospectively. Results . The main clinical manifestations were cough, expectoration in 56 cases (91.8%), shortness of breath, chest tightness in 48 cases (78.7%), fever in 61 cases (100%), muscle ache and weakness in 40 cases (65.6%), diarrhea or vomiting in 8 cases (13.1%), and headache in 4 cases (6.6%). After admission, the leukocyte count was normal in 40 cases (57.7%), higher in 9 cases (15.4%), and lower in 12 cases (26.9%). The lymphocyte count decreased in 53 cases (86.9%). CRP was increased in 29 cases (47.5%); PCT was increased in 15 cases (24.6%); ESR was increased in 38 cases (62.3%); D-dimer increased in 39 cases (63.9%); ALT/AST increased in 40 cases (65.6%); CK/CK-MB increased in 8 cases (13.1%); troponin I increased in 6 cases (9.8%); NT-proBNP increased in 35 cases (57.4%); IL-1 increased in 5 cases (8.2%); IL-2 receptor increased in 28 cases (45.9%); IL-6 increased in 23 cases (37.7%); IL-8 increased in 15 cases (24.6%); IL-10 increased in 12 cases (19.7%); and NTF increased in 22 cases (36.1%). The chest CT images showed that 38 cases (65.5%) of right lung lesions were more extensive than those of left lung lesions, 20 cases (34.5%) of left lung lesions were more extensive than those of right lung lesions, 42 cases (72.5%) of lower lobe lesions were more extensive than those of upper lobe lesions, 6 cases (10.3%) of upper lobe lesions were more extensive than those of lower lobe lesions, and 10 cases (17.2%) of upper and lower part lesions were roughly the same. Ground-glass opacity (GGO) was found in 12 cases (20.7%); GGO with focal consolidation in 38 cases (65.5%); small patchy edge fuzzy density increased in 24 cases (41.4%); large consolidation in 20 cases (34.5%); reticular or fibrous cord in 54 cases (93.1%); and air bronchogram in 8 cases (13.8%). Conclusions . COVID-19 patients in intensive care have no specific clinical manifestation and CT findings. However, analysis and summary of relevant data can help us assess the severity of the disease, decide the timing of treatment, and predict prognosis.